Juridical Analysis on the Possibility of Traffic Accident Victim Being Designated as Suspect - Effendi, Erdianto; Ardianto, Syaifullah Yophi; HB, Gusliana; Ishaq, Ishaq (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
The fundamental aim of criminal law is to shield society from potential victimization, allowing for the prosecution of wrongdoers, including the offenders engaged in negligent acts. This objective leads to a legal dilemma when negligence originates from the victim, sparking a debate within law enforcement about the entity to bear the criminal responsibility. Therefore, this study aimed to explore the juridical feasibility of designating victims as suspects in the same case where the offender has been victimized. Real cases were used in this study, accompanied by secondary data and interviews with crucial policymakers. The findings show that designating victims of negligence in traffic accidents as a suspect should not be pursued. Consequently, the investigation process should be suspended when the victim is found to be responsible for the accident, as the incident does not meet the criteria for a criminal act.